2007
DOI: 10.1097/mlg.0b013e3180337da6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Skull Base Chondroblastoma

Abstract: Gross total or near total resection of skull base chondroblastomas through lateral skull base approaches results in long-term tumor control and low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…There is insufficient data to predict tumor behavior in craniofacial chondroblastoma. Malignant degeneration to chondrosarcoma is likely rare but has been previously reported, 11 and some authors have suggested that lesions with an intratumoral aneurysmal bone cyst may behave more aggressively.…”
Section: 414546mentioning
confidence: 99%
“…There is insufficient data to predict tumor behavior in craniofacial chondroblastoma. Malignant degeneration to chondrosarcoma is likely rare but has been previously reported, 11 and some authors have suggested that lesions with an intratumoral aneurysmal bone cyst may behave more aggressively.…”
Section: 414546mentioning
confidence: 99%
“…The suture is anterosuperior to the external auditory canal and anatomically very close to TMJ [10]. Most patients with temporal bone chondroblastomas were older than those with tumors at the usual site, the ages ranged from 8 years to 85 years old, with a mean of 39.4 [4,11]. Of the 45 patients, 20 were male and 25 were female, and there was a variety of symptoms.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Most of these tumors commonly arise in the epiphysis of the long bones, and tumors of the temporal bones are extremely rare [1]. A chondroblastoma of the temporal bone was first reported by Denko and Krauel in 1955, and since then, around 70 cases have been reported [2][3][4]. We report a case of chondroblastoma of the temporal bone, and review the literature to discuss the clinical presentation, radiological and pathological findings, as well as surgical management strategies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations